Higher Frequency of CD4+CXCR5+ICOS+PD1+ T Follicular Helper Cells in Patients With Infectious Mononucleosis. Issue 45 (November 2015) - Liu, Jinlin; Zhou, Yonglie; Yu, Qinghua; Zhao, Zhao; Wang, Huan; Luo, Xiaoming; Chen, Yanxia; Zhu, Zhongliang; Chen, Guoqing; Wu, Mao; Qiu, Liannv
Abstract : Abstract: Follicular helper T (Tfh) cells are recognized as a distinct CD4 + helper T cell subset, and mainly dysregulated in the autoimmune disease, whether it plays a role in the infectious mononucleosis (IM) diseases is unknown. In this study, we found that the CD4 + CXCR5 + Tfh cells were not significantly changed, but the CD4 + CXCR5 + ICOS + and CD4 + CXCR5 + ICOS + PD1 + Tfh subsets were significantly increased in the IM patients, and all these cells were significantly changed after antiviral therapy. Second, only the numbers of CD4 + CXCR5 + ICOS + PD1 + Tfh cells correlated with the Epstein-Barr virus (EBV) DNA load, negatively correlated with the numbers of naive B cells and amount of IL-21, and positively correlated with the numbers of plasma cells, memory B cells, and atypical lymphocytes. Third, the frequency of CD4 + CXCR5 + ICOS + PD1 + Tfh subset was significantly higher in lymphadenectasis or hepatosplenomegaly patients, and associated with the level of alanine aminotransferase (ALT). All together, our findings discovered this CD4 + CXCR5 + ICOS + PD1 + Tfh cell subset might play an important role in the pathogenesis of IM.